The Influence of Leadership Style, Motivation and Discipline on Employee Performance at PT Sumo Internusa Indonesia - Naomi Frizilia Panggabean; Tm Safwan Fahri; Wisnu Gunawan; Hendry Hendry (Universitas Pendidikan Ganesha, 2021)
Human resources become the main role in every activity of a company. Although the company has a good infrastructure and facilities but without the support of human resources that are better than the activities of the company will not run properly and is difficult to achieve company goals. This study aims analyze the influence of Leadership Style, Motivation and Discipline on Employee Performance at PT Sumo Internusa Indonesia. Leadership style still can encourage or motivate the employees to work more actively, effectively, efficiently and optimally. Lack of motivation of employees in the company are visible from at least giving a salary increase, a promotion, giving an increase in incentives as well as the rise of the craft of money. Employees have less work discipline of the presence of employees’ delay. The performance of the employees looks of not achieving the target company. Research methods conducted is quantitative. The number of population and sample in this study a total of 62 employees. The simultaneous and partial leadership style, motivation and the discipline has positive and significant effect on employee performance at PT Sumo Internusa Indonesia. Useful suggestions are the correct style of leadership that is able to motivate employees. Increase motivation, especially the salary increase. Improve the discipline by providing clear rules and sanctions in accordance with the degree of violation of the employee.